Validation of a didactic model evaluating the usability, usefulness and acceptability of psychological first aid teaching through simulation - Emeric Saguin; Julia Salomé; Benoît Favodon; Bertrand Lahutte; Frédérique Gignoux-Froment (BMC Medical Education)
Abstract Purpose To evaluate the effectiveness of simulation as a means to teach Psychological First Aid in Operations (PFA-O). We propose to use a model built on research in didactics to assess the factors which may or may not encourage trainers to adopt and embrace this teaching technique. Material and method We submitted a questionnaire to all PFA-O trainers working in France, comprising 15 criteria divided into three dimensions: usability, usefulness and acceptability. Correlation and regression analyses were applied to assess the links between these criteria, teacher motivation, and actual implementation of training courses. We also wanted to test the relevance of these criteria to predict motivation in a multiple linear regression model. Results 59 trainers, i.e. 52.68% of the national workforce, responded to the questionnaire. Correlation analysis showed good model consistency, with significant correlations between the 3 dimensions under evaluation (usability, usefulness and acceptability), between these dimensions and teacher motivation, and a strong correlation between teacher motivation and the number of introductory training sessions undertaken each year. The final model incorporating the 15 criteria showed an R2 coefficient of determination of 0.71 (i.e. 71%, F = 4.91, p < 0.001). Conclusion This didactic model is relevant to assessing the motivational factors which contribute to trainers’ adherence to medical simulation and provides a methodological basis to evaluate the ergonomics of an educational tool in the field of health care. These findings suggest its applicability to a wider range of educational contexts beyond the military.